A path dependency behind Singapore's grade-oriented education system - Quek, Pearlyn Zi Ching (2016)
The term of a holistic education system has been constantly ringing in the ears of Singaporeans. However, no matter how hard the government tries to persuade Singaporeans that academic grades is not the only path for success, Singaporeans’ obsessions for grades persisted. Through the lens of historical institutionalism, the paper seeks to find out how path dependencies policies found in the system that have contributed to Singapore’s longstanding grade-oriented education system. Singapore’s education system might have undergone a series of reforms, but enduring features such as elitist hiring process, national examination and grades as a way to uphold Singapore’s meritocracy, and preference for elites in the education system remains. These practices could be stemmed from leaders’ belief that Singapore’s survival is crucially tied to the availability of talent at helm of the system. Therefore, despite the series of education reforms, these contradictory and path dependence policies consistently reinforce Singaporeans’ perceptions on the importance of academic grades.